2021
DOI: 10.1021/acs.est.1c04500
|View full text |Cite
|
Sign up to set email alerts
|

p-Phenylenediamine Antioxidants in PM2.5: The Underestimated Urban Air Pollutants

Abstract: The wide use and continuous abrasion of rubber-related products appears to be leading to an incredible release of p-phenylenediamine (PPD) antioxidants in the environment. However, no related research has been conducted on the pollution characteristics and potential health risks of PM 2.5 -bound PPDs. We report for the first time the ubiquitous distributions of six emerging PPDs and a quinone derivative, N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine quinone (6PPDQ), in PM 2.5 from urban areas of China. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 39 publications
3
73
1
Order By: Relevance
“… 4 In another study, Zhang et al evaluated the level of PPDs in PM 2.5 among six different cities in China and found remarkable intercity distinctions. 7 Their results found that the levels of 77PD were comparable or even higher than 6PPD in the investigated six cities. Considering this, we speculated that 77PD-Q may also occur in PM 2.5 collected from highly polluted areas/cities.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“… 4 In another study, Zhang et al evaluated the level of PPDs in PM 2.5 among six different cities in China and found remarkable intercity distinctions. 7 Their results found that the levels of 77PD were comparable or even higher than 6PPD in the investigated six cities. Considering this, we speculated that 77PD-Q may also occur in PM 2.5 collected from highly polluted areas/cities.…”
Section: Resultsmentioning
confidence: 86%
“… 37 Our results are in line with these earlier studies and suggest that traffic intensity may be a possible factor affecting the emission of PPD-Qs to the environment. 7 , 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After environmental release, TWPs enter soils, sediments, or surface waters and become persistent contaminant sources, including some extensively investigated contaminants like metals and PAHs. Presently, knowledge concerning TWP-derived emerging contaminants and related transformation products (TPs) is fragmentary and incomplete, although researchers are gradually narrowing this gap. Recently, 6PPD-quinone (6PPDQ), a TP of the common antioxidant 6PPD ( N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine), was reported to induce acute toxicity and mortality to coho salmon ( Oncorhynchus kisutch) at concentrations even below 100 ng/L. , To our knowledge, 6PPD is used in all passenger and commercial vehicle tires (0.4%–2% by rubber mass) to provide critical antiozonant and antioxidant functions at tire rubber surfaces. 6PPD and some related TPs, including 6PPDQ, were recently reported in roadway-derived particles and dusts. ,,, Given the global ubiquity of TWPs in roadway runoff and surface waters , and their toxicological relevance, , there exists an urgent need to characterize TWP-derived TPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a quinone derivative of the tire rubber antioxidant N -(1,3-dimethylbutyl)- N ′-phenyl-PPD (6PPD) formed by oxidative transformation, termed 6PPD-quinone, has attracted considerable international attention on PPDs because 6PPD-quinone was identified as the toxicant responsible for acute mortality in the Pacific Northwest coho salmon . Subsequent studies have confirmed the ubiquitous occurrence of 6PPD and 6PPD-quinone in stormwater runoff, surface waters, air particles, and dust. The same pathway may also produce quinones from other PPDs. A more recent study provided new evidence of multiple PPD-derived quinones in environmental media .…”
Section: Introductionmentioning
confidence: 99%